Diffusion and transfer of knowledge in agriculture - Huyghe , Christian; Bergeret , Pascal; Svedin , Uno (éditions Quae, 2016)
This book focuses on innovation in the agri-food system and the new paradigm drawn by bioeconomic approaches and principles. It draws on contributions presented during the 29th EURAGRI annual conference held in Luxemburg (September 2015) as well as on other workshops organised as part of EURAGRI. EURAGRI is an informal gathering of EU research and higher education organisations and ministries interested in agri-food research. It works as a platform of exchange and discussion on topics of common interest pertaining to the organisation, orientation and outlook of agri-food research in Europe in connection with global changes.